A phase II randomized placebo-controlled trial of omega-3 fatty acids for the treatment of acute lung injury* - Renee D. Stapleton; Thomas R. Martin; Noel S. Weiss; Joseph J. Crowley; Stephanie J. Gundel; Avery B. Nathens; Saadia Akhtar; John Ruzinski; Ellen Caldwell; J. Randall Curtis; Daren K. Heyland; Timothy R. Watkins; et al. (2011)
Objectives: Administration of eicosapentaenoic acid and docosahexanoic acid, omega-3 fatty acids in fish oil, has been associated with improved patient outcomes in acute lung injury when studied in a commercial enteral formula. However, fish oil has not been tested independently in acute lung injury. We therefore sought to determine whether enteral fish oil alone would reduce pulmonary and systemic inflammation in patients with acute lung injury. Design: Phase II randomized controlled trial. Setting: Five North American medical centers. Patients: Mechanically ventilated patients with acute lung injury ≥18 yrs of age. Interventions: Subjects were randomized to receive enteral fish oil (9.75 g eicosapentaenoic acid and 6.75 g docosahexanoic acid daily) or saline placebo for up to 14 days. Measurements and Main Results: Bronchoalveolar lavage fluid and blood were collected at baseline (day 0), day 4 ± 1, and day 8 ± 1. The primary end point was bronchoalveolar lavage fluid interleukin-8 levels. Forty-one participants received fish oil and 49 received placebo. Enteral fish oil administration was associated with increased serum eicosapentaenoic acid concentration (p < .0001). However, there was no significant difference in the change in bronchoalveolar lavage fluid interleukin-8 from baseline to day 4 (p = .37) or day 8 (p = .55) between treatment arms. There were no appreciable improvements in other bronchoalveolar lavage fluid or plasma biomarkers in the fish oil group compared with the control group. Similarly, organ failure score, ventilator-free days, intensive care unit-free days, and 60-day mortality did not differ between the groups. Conclusions: Fish oil did not reduce biomarkers of pulmonary or systemic inflammation in patients with acute lung injury, and the results do not support the conduct of a larger clinical trial in this population with this agent. This experimental approach is feasible for proof-of-concept studies evaluating new treatments for acute lung injury.